ON THE POSITIVE EXPERIENCE OF BASIC READING TEACHING DURING WEEKEND SCHOOL DAYS - O A Bejenari (Polylinguality and Transcultural Practices, 2017)
The article deals with problems in teaching compatriots children that live abroad, in particular in Italy. The author shares the successful experience of using teaching materials by Е.М. Chamraevaya, L.M. Samatovaya and V.V. Dronov.